Efficacy and Safety Evaluation of Sintilimab for Cancer Treatment: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Ye, Ziqi; Yang, Wenchao; Xuan, Bixia; Li, Xiaofang; He, Jiana; Si, Haiyan; Ma, Wenhua (Frontiers in Pharmacology, 2022)
Objective Meta analysis was used to explore the efficacy and safety of Sintilimab in the treatment of cancer. Methods The databases of CNKI, VIP, Wanfang Data, PubMed, ScienceDirect, the Cochrane Library and EMBASE were searched by computer to collect the randomized controlled trials published as of March 2022. The retrieval work was completed by two researchers alone. They screened the literature and extracted the data according to the nanodischarge standard, using revman5 4. The included studies were statistically analyzed. Results Six RCTs were included in this study, including 1048 cases of Sintilimab and 711 cases of other anticancer drugs. Compared with the control group, the overall survival (HR = 1.64, 95% CI: 1.35-1.99, P < 0.00001) and progression free survival (HR = 1.89, 95% CI: 1.59-2.25, P < 0.00001) of cancer treated with Sintilimab were longer and more effective. Moreover, the risk ratio of any grade of adverse reactions (HR = 0.87, 95% CI: 0.74-1.03, P = 0.11) and above grade III adverse reactions (HR = 0.84, 95% CI: 0.67-1.06, P = 0.14) in the treatment of cancer with Sintilimab was lower and the safety was better. Conclusion Compared with non-Sintilimab group, Sintilimab treatment can improve the clinical efficacy of tumor patients and has a lower incidence of adverse reactions. This treatment may be a promising treatment for cancer patients.